Developing an advanced high-tech entrepreneurial habitat - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
Technology, in and of itself, cannot transform ideas to profits. According to William Miller, a professor, entrepreneur and venture capitalist, having the technology that the market wants is only part of the game. To be successful, technology requires other necessary conditions to be in place – an ecosystem of talent, money, trade, education, art, even lawyers – to grow and flourish. The challenge, however, is in getting the hardware-software combination right.